Teachers Translanguaging Practice in Vocational EFL Classroom: An Observational Study - Ramadhani, Alya Usman; Maharsi, Ista (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2024)
This study aims to explore an EFL teacher's translanguaging practice when teaching English in a vocational high school. The participant of this study was a 43-year-old female teacher who has been teaching English for more than 10 years. Data were collected from a classroom video of 53 minutes. The video was transcribed and annotated using an observation checklist. Data were analyzed using thematic analysis. This study found that the teacher employed three translanguaging practices: code-switching, translation, and interpretation. Code-switching was used when the teacher delivered the lesson through a PowerPoint presentation, question and answer sessions, and instructing students to read or practice. Translation and interpretation were employed when the teacher helped the students comprehend the material. The teacher used English first, followed by comprehension sentences in the first or second language. The teacher also reformulated a sentence in English to help the students understand the materials well and easily. This study suggests that teachers' translanguaging practices enable teachers to clarify instructions, elaborate questions, and explain learning materials.